Trade Facilitation and Its Impacts on the Economic Welfare and Sustainable Development of the ECOWAS Region - Safaeimanesh, Shahrzad; Jenkins, Glenn P. (Mdpi, 2021)
The facilitation of trade is a principal objective in the context of increasing regional trade integration for the achievement of sustainable development goals. The purpose of this study is to estimate the potential annual economic gain to be had from trade facilitation by the coastal countries of the Economic Community of West African States (ECOWAS). These measures would decrease border and documentary compliance time and costs of the administration of international trade. A partial equilibrium welfare economics framework is used that employs sets of export supply and import demand elasticities for each country that are derived using a general equilibrium estimation method. The annual economic welfare gains resulting from the reduction of excessive trade compliance costs for the region are estimated to between US$1.6 billion to US$2.7 billion (2019 prices). This is between 0.24% and 0.42% of the combined GDPs of these countries. The welfare gain is between 6% and 10% of the combined governments' budgets assigned for education, and is between 33% and 58% of their budgets allocated for health. In the absence of reform, these inefficient practices waste an amount equal to between 15% and 26% of the annual net official development assistance these countries receive.
Keywords: trade facilitation; West Africa; Economic Community of West African States (ECOWAS); regional integration; trade compliance costs; trade reform; economic welfare gains; sustainable development; SDGs 2030